2014
DOI: 10.1310/hpj4907-644
|View full text |Cite
|
Sign up to set email alerts
|

Infusion-Related Reaction following Daptomycin Two-Minute Rapid Intravenous Administration

Abstract: A 2-minute intravenous injection of daptomycin in this patient yielded a reaction that was not present on rechallenge with standard, extended infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…At the outset of this study, the initial antibacterial screening was performed on methicillinresistant Staphylococcus aureus (MRSA, 2658 RCMB). The results presented in Table 1 indicated that the 2-amino-1,3,4oxadiazole linker with aliphatic side chains (compounds [8][9][10][11][12][13][14][15][16][17] is void of anti-MRSA activity.…”
Section: Biological Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the outset of this study, the initial antibacterial screening was performed on methicillinresistant Staphylococcus aureus (MRSA, 2658 RCMB). The results presented in Table 1 indicated that the 2-amino-1,3,4oxadiazole linker with aliphatic side chains (compounds [8][9][10][11][12][13][14][15][16][17] is void of anti-MRSA activity.…”
Section: Biological Results and Discussionmentioning
confidence: 99%
“…So far, most of the newly-introduced antibiotics, such as cearoline 16 and lipoglycopeptides are taken parenterally. 17 When phenylthiazoles were rst discovered, their main drawback was the extremely short plasma half-life of the early generation, for which the t 1/2 of the lead compound 1 (Fig. 1) was only 29 minutes.…”
Section: 23mentioning
confidence: 99%
“…A case report previously described erythroderma developing 2 hours after the first 650 mg dose (6 mg/kg) of daptomycin given as a 2-minute infusion. 9 The reaction included redness and warmth around the face next and upper back 2 hours after the infusion. On further administration, erythroderma did not recur.…”
Section: Discussionmentioning
confidence: 99%
“…Any patient with a potential IRR was assessed and scored using the Naranjo algorithm. 10 All identified IRRs were adjudicated blinded to administration method by 2 clinical pharmacy specialists.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation